Binge-watching: Video-on-demand, quality TV and mainstreaming fandom. (May 2017) - Jenner, Mareike
This article explores the concept of the binge as viewing protocol associated with fan practices, industry practice and linked to 'cult' and 'quality' serialised content. Viewing binge-watching as an intersection of discourses of industry, audience and text, the concept is analysed here as shaped by a range of issues that dominate the contemporary media landscape. In this, factors like technological developments, fan discourses and practices being adopted as 'mainstream' media practice, changes in the discursive construction of 'television' and an emerging video-on-demand industry contribute to the construction of binge-watching as deliberate, self-scheduled alternative to 'watching TV'.